Pandangan mahasiswa tentang kesetaraan gender di lingkungan kampus - Ayuning Tyas, Citra Hapsari (Maliki Interdisciplinary Journal, 2025)
Gender equality is one of the crucial issues that has gained significant attention in higher education. This study aims to analyze students’ perspectives on gender equality within the campus environment and the factors that influence them. The research employed a descriptive literature study method by reviewing various previous studies relevant to gender equality in the context of higher education. The findings indicate that students have a relatively good awareness of the importance of gender equality, although its implementation on campus remains limited. Gender stereotypes are still evident, particularly in organizational roles and academic participation, where male students tend to dominate leadership positions while female students are more often placed in administrative roles. Moreover, students’ perspectives are also shaped by external factors such as family upbringing, local cultural traditions, and exposure to social media. In conclusion, although students’ awareness of gender equality is relatively high, structural and cultural barriers continue to exist. This study recommends strengthening gender-responsive campus policies and encouraging students to be more critical in rejecting gender stereotypes in academic settings.